Find and explain the error in the student's work/answers below

Solve:
m²+m-6=0
m^2-2m +3m-6=0
m(m-2)+3(m-2)=0
(m-2)(m+3) =0
m-2=0orm+3=0
m =-2orm=3

1 answer

The error in the student's work is the last step where they split the equation into two separate equations incorrectly. The correct step would be to split it as "m - 2 = 0 or m + 3 = 0", not "m = -2 or m = 3".
Similar Questions
  1. Find and explain the error in the​ student’s work below.​Solve: 2m² - 7m​ - 30​ = 0 2m² + 5m​ - 12m​ - 30​ = 0
    1. answers icon 1 answer
  2. Find and explain the error in the student's work below.Solve: 2c^2+c-6=0 2c²+ 4c-3c -6=0 2c(c + 2)- 3(c+2)=0 (c+2)(2c-3)=0 The
    1. answers icon 1 answer
  3. Find and explain the error in the​ student’s work/answer below.​Solve: ​ 2c² + c​ – 6​ = 0 ​ 2c² + 4c​ –
    1. answers icon 1 answer
  4. Find and explain the error in the​ student’s work/answers below.​Solve: ​ m² + m​ – 6​ = 0 ​ m² – 2m​ +
    1. answers icon 3 answers
more similar questions